The Community In-Reach and Care Transition (CIRACT) clinical and cost-effectiveness study: study protocol for a randomised controlled trial - Watson, Alison; Charlesworth, Lisa; Jacob, Ruth; Kendrick, Denise; Logan, Philippa; Marshall, Fiona; Montgomery, Alan; Sach, Tracey; Tan, Wei; Walker, Marion; Waring, Justin; Whitham, Diane; et al. (BioMed Central, 2015)
Background